Pengaruh Efisiensi Kinerja Perbankan Syariah di Indonesia dan Malaysia Menggunakan Metode DEA - Asyaffa Aulia, Prambawati; Sholahuddin, Muhammad; Imronudin (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to analyze and compare the operational efficiency of sharia banking in Indonesia and Malaysia using the Data Envelopment Analysis (DEA) method, a non-parametric approach that is able to measure relative efficiency based on input and output. The research gap lies in the lack of comparative analysis of Islamic banking efficiency in the two countries, especially using the DEA method. The research sample consists of sharia banking financial reports in Indonesia and Malaysia during the 2019–2023 period. The research results show that both countries have a high level of technical efficiency, with an average efficiency close to 1. Bank B in Indonesia and Bank F in Malaysia show stable efficiency performance, while Bank D shows significant fluctuations. Further analysis reveals that there is no significant difference in operational efficiency between the two countries. This research contributes by providing in-depth insight into the efficiency of sharia banking and becomes a reference for regulators and banking managers in improving operational strategies. Research limitations include limited data coverage on financial variables and certain periods. For future research, it is recommended to include non-financial variables and expand the analysis period.